In vitro activity and mode of action of the antimicrobial peptide CPF-P2 against Escherichia coli ATCC 700928 - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2025)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.